Managing welfare reform in New York City - Savas, Emanuel S. (Rowman & Littlefield Publishers)
Introduction to welfare reform under Mayor Giuliani / by E.S. Savas -- Overview of welfare reform / by Demetra Smith Nightingale -- Changing the organizational culture / by Arthur L. Levine -- Protecting against welfare fraud / by James Clark -- Managing the welfare system with JobStat / by Kay E. Sherwood -- Achieving "full engagement" / by Douglas J. Besharov and Peter Germanis -- Putting welfare applicants and recipients to work in the work experience program / by James Clark -- Placing welfare applicants and recipients in jobs through performance-based contracting / by Burt S. Barnow and John Trutko -- Engaging drug and alcohol abusers / by Sally Satel -- Housing the homeless / by Thomas J. Main -- The welfare revolution in New York City / by June O'Neill and Sanders Korenman -- Reflections of the commissioner / by Jason A. Turner.